THE LEGAL STATUS OF CERTIFICATES OF CULTIVATION RIGHTS IN THE CONTEXT OF CONSTITUTIONAL LAW: AN ANALYSIS OF CASE DECISION NUMBER 4655 K/Pdt/2023 - Kristina Salmah, Maria; Siregar, Muhammad Sahdan; Yanuarto, Aldo; Wahyudi, Dody (KLAUSULA (Jurnal Hukum Tata Negara Adminitrasi Dan Pidana), 2024)
This research discusses the legal strength of Cultivation Rights Certificates in the context of Constitutional Law, with a focus on the case study of decision Number 4655 K/Pdt/2023. Cultivation rights are contained in Law Number 5 of 1960 concerning Basic Agrarian Principles in Article 28 Paragraph 1. This right gives authority to manage land controlled by the state within a certain period for business purposes in the agricultural sector, fisheries, and animal husbandry. In this case, PT Sarana Subur Agrindotama and the Head of the Provincial State Land Agency as well as the Head of the Regency State Land Agency in the case area sued Muhammad Noor (deceased) for allegedly committing an unlawful act. This research uses a normative analysis approach to explore legal aspects related to the legal strength of Cultivation Rights certificates, as well as their impact on legal certainty in the control and management of land rights. The findings show that procedural Cultivation Rights Certificates as authentic evidence play an important role in protecting the rights of holders of Cultivation Rights Certificates. This ruling also has significant implications for legal practice and land policy in Indonesia and emphasizes the importance of ownership of original documents in land disputes. Thus, this article contributes to the understanding of the relationship between constitutional law and ownership of land rights.